The generation of scenes in Mixed Reality environments using the chromakey technique - Rodrigues Sanches, Silvio Ricardo; Sementille, Antonio Carlos [UNESP]; Rodello, Ildelberto Aparecido; Ferreira Brega, Jose Remo [UNESP]; Brooks, T.; Ikei, Y.; Petersson, E.; Haller, M.; Kim, G. J.; Noma, H. (Ieee Computer Soc, 2007)
A classic problem in the development of Mixed Reality systems is the registration. The correct alignment between virtual objects and the real elements is extremely important for the coherent composition of the resultant scene. Considering this context, this paper describes an approach for the composition of scenes in Mixed Reality environments using the chromakey technique for the extraction of real objects. After that, the scene is mounted in a coherent way related to the depth in OpenGL frame buffer for posterior rendering.